Salmonella Typhi and Salmonella Paratyphi prevalence, antimicrobial susceptibility profile and factors associated with enteric fever infection in Bahir Dar, Ethiopia - Tadele Amsalu (Nature Portfolio, 2021)
Abstract Enteric fever (EF) is caused by Salmonella enterica serovars Typhi (S. Typhi) and Paratyphi (S. Paratyphi) causing significant health problems in developing countries including Ethiopia. Thus present study aimed to determine prevalence and antimicrobial resistance profile of S. Typhi and S. Paratyphi among EF suspected patients at Felege-Hiwot comprehensive specialized hospital, Bahir Dar, Ethiopia. Hospital based cross-sectional study was conducted from March-to-May 2020. Totally, 150 patients were included conveniently. Data were collected using questionnaires by face-to-face interview. Concurrently, venous blood and stool specimens were collected and processed following standard bacteriological technique. Antimicrobial susceptibility test (AST) was performed by disc diffusion method. Logistic regression was performed to identify factors associated with EF infection. The study indicated 5.3% EF prevalence where S. Typhi accounted 75%. S. Typhi and S. Paratyphi isolates were 100% sensitive to cephalosporins but at least 83.3% showed resistance against chloramphenicol and tetracycline. At least 66.7% of isolates were multidrug resistance (MDR). Using well water for drinking (AOR = 6.22, CI 1.4–27.5) and previous EF history (AOR = 10.74, CI 2.01–55.9) were significantly associated with EF infection. Thus high bacterial prevalence and MDR isolates was observed. Therefore, health professionals should consider AST and use antibiotics with cautions for EF patient management.